Implementasi Kebijakan Penggunaan Aplikasi Sistem Informasi Manajemen Pengadaan Langsung (Simpel) Di Univeristas Sriwijaya - Moulina, Widia; Sulastri, Sri; Zuber, Konar (Program Studi Magister Ilmu Administrasi Publik STISIPOL Candradimuka, 2023)
This reaseach to analyze the Policy Implementation of the Use of Direct Procurement Management Information System (SIMPeL) at Sriwijaya University. information system in the procurement of goods and services in government agencies developed by the Secretariat General of the Ministry of Finance (Kemenkeu). The Direct Procurement Management Information System (SIMPeL) is an information system developed by the Ministry of Finance to facilitate the direct procurement process. This system functions to manage a database of direct procurement results, in order to produce appropriate information for the preparation of spending analysis, standard cost analysis, direct procurement implementation reports, and other managerial reports according to the needs and applicable regulations. This research is a qualitative research with a case study approach with interview, observation, and document analysis methods for data collection. The results of this study indicate that the overall use at Sriwijaya University has helped users in carrying out the direct procurement process, but it is not yet optimal.